Pengaruh Lingkungan Kerja dan Motivasi Terhadap Kinerja Aparatur Sipil Negara di Lingkungan Kantor Walikota Pematangsiantar - hengki mangiring parulian simarmata; Doris Yolanda Saragih; Poltak Pardamean Simarmata (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
This research aims to analyze the influence of environment and working motivation on employee performance of Pematangsiantar mayor's office. The research method use quantitative. The sample of the research is 100 people by using purposive sampling. The data were tested with validity and reliability test with SPSS. The data analysis with multiple linear regression method.The result statistic showed the influence of environment and work motivation on employee performance are positif significant with R Square 78.1%. The 21.9% influenced by other factor outside of the variabel.